Octreotide use and safety in infants with hyperinsulinism - McMahon, Ann W. (Pharmacoepidemiol Drug Saf, 2016)
BACKGROUND: Octreotide is a synthetic peptide analog of naturally occurring somatostatin. Octreotide is used off-label in children <6 years of age for hyperinsulinism, chylothorax, and gastrointestinal bleeding. There is a lack of controlled data on efficacy or potential adverse events from this off-label use. METHODS: Three pediatric hospitals participated in this study. Patients were hospitalized January 2007–December 2010 and administered octreotide for congenital hyperinsulinism (CHI) at least 1 day. Variables assessed included octreotide dosage, patient demographics, medical interventions, concomitant medicines, serious adverse events (SAEs) including necrotizing enterocolitis (NEC), and mortality. RESULTS: The 103 patient sample had a median gestational age of 38 weeks. During the study period, two patients died: one from NEC and the other from cardiomyopathy/sepsis. There were 11 other SAEs in the 101 surviving patients. CONCLUSION: This study highlights potential risks in administering octreotide off-label. This study, like several other published studies, has highlighted NEC in a full-term infant treated with octreotide. It is important to study the efficacy and the safety of octreotide for hyperinsulinism. In the interim, it might be prudent to prescribe octreotide in CHI neonates only in the absence of other risk factors for NEC.